A seamless welded thermal insulation strip for aluminum doors and windows and a preparation method thereof
By blending antioxidants, lubricants, graft solubilizers, car water tank recycling PA66 material and black sand with PA10T resin and modified glass fiber, the poor processing performance problem caused by high viscosity of PA10T melt is solved, and efficient molding of the insulation strip and excellent heat resistance are achieved.
Patent Information
- Application Number
- CN202510025834.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The high melt viscosity of PA10T during melt processing leads to poor processing performance of the material and difficult to form and process.
After premixing antioxidants, lubricants, graft solubilizers, car water tank recycling PA66 material and black sand, blending them with PA10T resin and modified glass fiber, extruded and granulated, dried, and molded to obtain seamless welded broken bridge aluminum door and window insulation strips.
It improves the processing fluidity of the material, improves the heat resistance and mechanical properties of the heat insulation strips, and reduces the degradation efficiency of PA10T in high-temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic materials, and in particular to a seamless welded thermal insulation strip for aluminum doors and windows and a preparation method thereof. Background Art
[0002] As the living environment becomes more energy-saving and high-end, people's energy-saving awareness is becoming more and more obvious, and the demand for energy-saving buildings is getting higher and higher. Ordinary aluminum alloy building profiles can no longer meet the energy-saving needs of existing buildings, and thermal insulation aluminum profiles with energy-saving functions have come into being. As a new type of energy-saving building material, thermal insulation aluminum profiles have been highly recognized by the market due to their excellent energy-saving effects. The quality of their core component, nylon insulation strips, is crucial. Seamless welded thermal insulation aluminum doors and windows use arc-shaped chamfer welding, which not only has beautiful visual effects, but also has excellent air tightness, waterproof performance, firmness and good quietness, making it a trend in the development of high-end thermal insulation aluminum doors and windows. Seamless welded thermal insulation aluminum doors and windows have higher requirements for the high-temperature resistance of the insulation strips due to the installation-first-then-welding process. They need to withstand baking at 250℃ for 4 hours without deformation or blistering.
[0003] High-performance insulation strips are generally made through two processes: one is the twin-screw granulation process modified by glass fiber reinforced nylon 66 composite materials, and the other is the single-screw extrusion molding process; the insulation strips made of glass fiber reinforced PA66 are limited to high-end aluminum doors and windows because PA66 is an aliphatic polyamide with a maximum tolerance temperature of only 230°C. Polydecane terephthalamide (PA10T) is a new type of high-temperature resistant semi-aromatic PA, which is formed by polycondensation of terephthalic acid and decanediamine. Compared with other aliphatic PAs, it not only retains the excellent mechanical properties, friction resistance and organic solvent resistance of traditional nylon, but also greatly improves its heat resistance and significantly reduces its water absorption performance with the introduction of benzene rings. However, the high melt viscosity of PA10T during melt processing leads to poor processing performance of the material, difficult molding processing, and difficulty in injection molding to obtain products with good performance, thus limiting the application of PA10T. Summary of the invention
[0004] The purpose of the present invention is to provide a seamless welded thermal insulation strip for aluminum doors and windows and a preparation method thereof, so as to solve the following technical problems: PA10T has a high melt viscosity during melting processing, resulting in poor processing performance of the material and difficulty in molding processing.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows, comprising the following steps:
[0007] A1: According to the proportion of raw material components, antioxidant, lubricant, grafting solubilizer, PA66 material recycled from automobile water tank and black sand are premixed, and then PA10T resin and glass fiber are added for blending, extruded into granules and dried to obtain alloy material;
[0008] A2: Molding the alloy material to obtain seamless welded thermal insulation strips for aluminum doors and windows;
[0009] The preparation method of modified glass fiber comprises the following steps:
[0010] A1: Add vinyl glass fiber, tetrahydrofuran, 2-mercaptoethanol and azobisisobutyronitrile into a reaction kettle and disperse them evenly. Control the temperature to 50-60°C, keep the temperature to react for 2-4 hours, filter, wash and dry to obtain component 1.
[0011] A2: In a nitrogen atmosphere, the component 1, toluene, isophorone diisocyanate and dibutyltin dilaurate are added into a reaction kettle and dispersed evenly. The temperature is controlled at 30-45° C., and the reaction is kept warm for 4-8 hours. The mixture is filtered and dried to obtain the component 2.
[0012] A3: Add the component 2, 4,4'-methylenebis(2,6-di-tert-butylphenol), triethylamine and toluene into a reaction kettle and disperse them evenly. Control the temperature to 70-80°C and keep the reaction for 4-8 hours. Rotary evaporate to remove the solvent and dry to obtain modified glass fiber.
[0013] Preferably, the addition ratio of vinyl glass fiber, tetrahydrofuran, 2-mercaptoethanol and azobisisobutyronitrile in A1 is 10 g: 20-40 mL: 1-4 g: 0.1-0.3 g.
[0014] Preferably, the addition ratio of component 1, toluene, isophorone diisocyanate and dibutyltin dilaurate in A2 is 10 g: 50-100 mL: 2-4 g: 0.05-0.15 g.
[0015] Preferably, the addition ratio of component 2, 4,4'-methylenebis(2,6-di-tert-butylphenol), triethylamine and toluene in A3 is 10 g: 3-6 g: 0.05-0.15 g: 50-100 mL.
[0016] Preferably, the preparation method of vinyl glass fiber comprises the following steps: adding glass fiber, deionized water, anhydrous ethanol and vinyl trimethoxysilane into a reaction kettle, controlling the temperature at 50-60° C., heat preservation for 3-6 hours, washing and drying to obtain vinyl glass fiber.
[0017] Preferably, the addition ratio of glass fiber, deionized water, anhydrous ethanol and vinyltrimethoxysilane is 10 g: 5-10 mL: 45-90 mL: 3-6 g.
[0018] Preferably, the modified glass fiber accounts for 24.0-24.5% of the total mass of the thermal insulation strip.
[0019] Preferably, PA10T resin accounts for 51.2-55.6% of the total mass of the thermal insulation strip.
[0020] Preferably, the specific process of extrusion granulation in the preparation process of the alloy material is: adding the raw materials of the alloy material to a twin-screw extruder, and controlling the extrusion temperature of the twin-screw extruder to 280-320° C. and the extruder speed to 350-400 rpm.
[0021] Preferably, the specific process of molding is: adding the alloy material to the main feeding port of the single-screw insulation strip extruder, controlling the process temperature at 280-340°C, shaping with an I-type mold, and controlling the cooling temperature at 30-45°C to obtain a seamless welded thermal insulation strip for broken aluminum doors and windows.
[0022] Preferably, the grafted solubilizer is maleic anhydride grafted ethylene octene copolymer elastomer; the grafted solubilizer accounts for 3.5-6.0% of the total mass of the thermal insulation strip.
[0023] Preferably, the preparation method of the graft solubilizer comprises the following steps: adding ethylene-1-octene copolymer, maleic anhydride and initiator into a twin-screw extruder, melt-extruding and granulating to obtain the graft solubilizer.
[0024] Preferably, the initiator is dicumyl peroxide; the grafting solubilizer comprises the following raw materials in weight percentage: 0.8-1.5% maleic anhydride, 0.04-0.1% initiator dicumyl peroxide, and the balance is ethylene-1-octene copolymer; the sum of the raw materials weight percentages is 100%.
[0025] Preferably, the extrusion temperature of the twin-screw extruder during the preparation of the grafting solubilizer is 180-190°C.
[0026] Preferably, the preparation method of automobile radiator recycled PA66 material comprises the following steps: automobile radiator recycled particles are mixed with diepoxy group chain extender EP and antioxidant, and then added into a twin-screw extruder for extrusion and granulation to obtain automobile radiator recycled PA66 material; automobile radiator recycled PA66 material accounts for 18.3-19.8% of the total mass of the thermal insulation strip.
[0027] Preferably, the antioxidant 1 is a hindered phenol antioxidant or a phosphite antioxidant; the automobile water tank recycled PA66 material includes the following raw materials in weight percentage: 1-3% diepoxy group chain extender EP, 0.1-0.5% antioxidant 1, and the remainder is automobile water tank recycled particles; the sum of the weight percentages is 100%.
[0028] Preferably, during the preparation of the PA66 material recycled from automobile water tanks, the speed of the twin-screw extruder is 200-500 rpm and the extrusion temperature is 240-270°C.
[0029] Preferably, the preparation method of automobile water tank recycling particles comprises the following steps: unpacking the recycled automobile water tank, roughly sorting to remove large impurities, magnetic metals, and non-magnetic metals, manually sorting, wet crushing, hot alkaline water washing to remove oil stains, drying, electrostatic sorting, infrared and color fine sorting, and warehousing and homogenization to obtain automobile water tank recycling particles.
[0030] Preferably, the lubricant is any one of stearic acid, metal stearate, olefin wax lubricant, oleamide, and ethylene bis stearamide; the lubricant accounts for 0.2-0.4% of the total mass of the thermal insulation strip. The lubricant added in the present application reduces the friction between plastic molecules and between plastic molecules and the surface of the equipment.
[0031] Preferably, the antioxidant is a hindered phenol antioxidant; the antioxidant accounts for 0.1-0.2% of the total mass of the thermal insulation strip. The hindered phenol antioxidant added in the present application can capture free radicals generated when the plastic is degraded or decomposed, thereby slowing down the degradation or decomposition rate of the plastic.
[0032] Preferably, the black sand is organic carbon black obtained by treating carbon black with a silane coupling agent; the black sand accounts for 0.3-0.8% of the total mass of the thermal insulation strip.
[0033] Preferably, the method for preparing organic carbon black comprises the following steps: after blending the solvent and the silane coupling agent, adding carbon black, controlling the temperature at 60-70° C., keeping the temperature for reaction for 10-30 min, filtering, extracting and drying to obtain organic carbon black.
[0034] Preferably, the solvent is a mixture of isopropanol and water in a volume ratio of 3:1; the addition ratio of solvent: silane coupling agent: carbon black is 200-300 mL: 2.5-7.5 g: 100 g.
[0035] A seamless welded thermally-insulated aluminum door and window strip, made by any one of the above-mentioned preparation methods.
[0036] Beneficial effects of the present invention:
[0037] (1) The present application uses vinyl trimethoxysilane to perform organic treatment on glass fiber to obtain vinyl glass fiber; and uses the mercapto group of 2-mercaptoethanol to undergo a click reaction with the vinyl group of the vinyl glass fiber to obtain component one; then uses isophorone diisocyanate to undergo a nucleophilic addition reaction with component one to graft isocyanate groups on the surface of the glass fiber to obtain component two; finally, the present application uses the isocyanate groups on component two to undergo a nucleophilic addition reaction with 4,4'-methylenebis(2,6-di-tert-butylphenol) to obtain modified glass fiber.
[0038] The present application modifies the glass fiber, and the modified glass fiber is easy to be oriented. The modified glass fiber in the oriented area effectively reduces the entanglement of the molecular chain of the matrix resin, thereby reducing the melt viscosity of the matrix resin and improving the processing fluidity of the material; it also improves the problem of decreased processing fluidity caused by directly adding glass fiber to enhance the material. The modified glass fiber prepared in the present application is evenly dispersed in the composite material and has good interface adhesion with the PA10T matrix resin. When the material is subjected to external forces, the forces are transmitted to the modified glass fiber along the interface layer, and the tensile strength, bending modulus, notched impact strength, etc. of the material are significantly improved. The modified glass fiber prepared in the present application is added to the insulation strip material, which effectively reduces the degradation efficiency of PA10T in a hot oxygen environment and improves the heat resistance of the insulation strip.
[0039] (2) In the present application, maleic anhydride grafted ethylene octene copolymer elastomer is added as a grafting solubilizer to work synergistically with the modified glass fiber. When the material is subjected to external force, it can induce a large number of silver streaks and shear bands as the center of stress concentration, thereby consuming a large amount of energy and improving the impact strength of the material; the addition of the grafting solubilizer improves the compatibility of PA10T, PA66 materials recycled from automobile radiators and modified glass fibers to a certain extent, so that the reinforcing effect of the modified fiber can be better reflected. DETAILED DESCRIPTION
[0040] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1 The preparation method of the grafting solubilizing agent comprises the following steps:
[0042] 98.43 g of ethylene-1-octene copolymer (Engage 8150, purchased from DuPont Dow Specialty Polymers), 1.5 g of maleic anhydride and 0.07 g of dicumyl peroxide were added into a twin-screw extruder for melt extrusion and granulation. The extrusion temperature of the twin-screw extruder was 190° C. to obtain a grafting solubilizer.
[0043] The preparation method of organic carbon black comprises the following steps: after mixing 150 mL of isopropanol, 50 mL of water and 2.5-7.5 g of γ-aminopropyltriethoxysilane, adding 100 g of carbon black, controlling the temperature at 60-70° C., keeping the temperature for reaction for 10-30 min, filtering, extracting and drying to obtain organic carbon black.
[0044] The preparation method of PA66 material recycled from automobile water tank comprises the following steps:
[0045] A1: The preparation method of automobile water tank recycling particles comprises the following steps: unpacking the recycled automobile water tanks, roughly sorting to remove large impurities, magnetic metals, and non-magnetic metals, manually sorting, wet crushing, hot alkaline water washing to remove oil stains, drying, electrostatic sorting, infrared and color fine sorting, and warehousing and homogenization to obtain automobile water tank recycling particles;
[0046] A2: 97.8g of automobile water tank recycled particles were mixed with 2g of diepoxy group chain extender EP and 0.2g of antioxidant 1010, and then added into a twin-screw extruder for extrusion and granulation. The speed of the twin-screw extruder was 300rpm and the extrusion temperature was 260℃ to obtain automobile water tank recycled PA66 material.
[0047] Example 2 The preparation method of modified glass fiber comprises the following steps:
[0048] A1: 10g of glass fiber (chopped length 4mm, single fiber diameter 13um), 5mL of deionized water, 45mL of anhydrous ethanol, and 3g of vinyl trimethoxysilane were added into a reactor, the temperature was controlled at 50℃, the heat treatment was carried out for 3h, and then washed and dried to obtain vinyl glass fiber;
[0049] A2: 10 g vinyl glass fiber, 20 mL tetrahydrofuran, 1 g 2-mercaptoethanol, and 0.1 g azobisisobutyronitrile were added to a reaction kettle and dispersed evenly. The temperature was controlled at 50°C and the reaction was kept warm for 2 h. The mixture was filtered, washed, and dried to obtain component 1.
[0050] A3: In a nitrogen atmosphere, 10 g of component 1, 50 mL of toluene, 2 g of isophorone diisocyanate, and 0.05 g of dibutyltin dilaurate were added to a reaction kettle and dispersed evenly. The temperature was controlled at 30°C and the reaction was kept warm for 4 hours. The component 2 was obtained by suction filtration and drying.
[0051] A4: Add 10g of component 2, 3g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 0.05g of triethylamine and 50mL of toluene into a reaction kettle and disperse them evenly. Control the temperature to 70°C and keep the reaction for 8h. Rotary evaporate to remove the solvent and dry to obtain modified glass fiber.
[0052] Example 3 The preparation method of modified glass fiber comprises the following steps:
[0053] A1: 10g of glass fiber (chopped length 4mm, single fiber diameter 13um), 10mL of deionized water, 90mL of anhydrous ethanol, and 6g of vinyl trimethoxysilane were added into a reactor, the temperature was controlled at 55℃, the heat treatment was carried out for 4h, and then washed and dried to obtain vinyl glass fiber;
[0054] A2: 10 g vinyl glass fiber, 30 mL tetrahydrofuran, 2.5 g 2-mercaptoethanol, and 0.2 g azobisisobutyronitrile were added to a reaction kettle and dispersed evenly. The temperature was controlled at 55°C and the reaction was kept warm for 3 h. The mixture was filtered, washed, and dried to obtain component 1.
[0055] A3: In a nitrogen atmosphere, 10 g of component 1, 60 mL of toluene, 3 g of isophorone diisocyanate, and 0.1 g of dibutyltin dilaurate were added to a reaction kettle and dispersed evenly. The temperature was controlled at 40°C and the reaction was kept warm for 6 hours. The component 2 was obtained by suction filtration and drying.
[0056] A4: Add 10g of component 2, 4g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 0.1g of triethylamine and 100mL of toluene into a reaction kettle and disperse them evenly. Control the temperature to 75°C and keep the reaction for 8h. Rotary evaporate to remove the solvent and dry to obtain modified glass fiber.
[0057] Example 4 The preparation method of modified glass fiber comprises the following steps:
[0058] A1: 10g of glass fiber (chopped length 4mm, single fiber diameter 13um), 10mL of deionized water, 90mL of anhydrous ethanol, and 6g of vinyl trimethoxysilane were added into a reactor, the temperature was controlled at 60℃, the heat treatment was carried out for 6h, and then washed and dried to obtain vinyl glass fiber;
[0059] A2: 10 g vinyl glass fiber, 40 mL tetrahydrofuran, 4 g 2-mercaptoethanol, and 0.3 g azobisisobutyronitrile were added to a reaction kettle and dispersed evenly. The temperature was controlled at 60°C and the reaction was kept warm for 4 h. The mixture was filtered, washed, and dried to obtain component 1.
[0060] A3: In a nitrogen atmosphere, 10 g of component 1, 100 mL of toluene, 4 g of isophorone diisocyanate, and 0.15 g of dibutyltin dilaurate were added to a reaction kettle and dispersed evenly. The temperature was controlled at 45°C, and the reaction was kept warm for 8 hours. The mixture was filtered and dried to obtain component 2.
[0061] A4: Add 10g of component 2, 6g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 0.15g of triethylamine and 100mL of toluene into a reaction kettle and disperse them evenly. Control the temperature to 80°C and keep the reaction for 8h. Rotary evaporate to remove the solvent and dry to obtain modified glass fiber.
[0062] Example 5 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0063] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0064] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Example 2 was fed into the second side feed port, blended, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0065] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0066] Example 6 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0067] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0068] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Example 3 was fed into the second side feed port, blended, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0069] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0070] Example 7 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0071] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0072] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Example 4 was fed into the second side feed port, blended, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0073] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0074] Comparative Example 1 The preparation method of modified glass fiber comprises the following steps:
[0075] A1: 10g of glass fiber (chopped length 4mm, single fiber diameter 13um), 10mL of deionized water, 90mL of anhydrous ethanol, and 6g of vinyl trimethoxysilane were added into a reactor, the temperature was controlled at 55℃, the heat treatment was carried out for 4h, and then washed and dried to obtain vinyl glass fiber;
[0076] A2: 10 g vinyl glass fiber, 30 mL tetrahydrofuran, 2.5 g 2-mercaptoethanol, and 0.2 g azobisisobutyronitrile were added to a reaction kettle and dispersed evenly. The temperature was controlled at 55°C and the reaction was kept warm for 3 h. The mixture was filtered, washed, and dried to obtain component 1.
[0077] A3: In a nitrogen atmosphere, 10 g of component 1, 60 mL of toluene, 3 g of isophorone diisocyanate, and 0.1 g of dibutyltin dilaurate were added to a reaction kettle and dispersed evenly. The temperature was controlled at 40°C and the reaction was kept warm for 6 hours. The component 2 was obtained by suction filtration and drying.
[0078] A4: 10 g of component 2 and 4 g of 4,4'-methylenebis(2,6-di-tert-butylphenol) were blended to obtain modified glass fiber.
[0079] Comparative Example 2 The preparation method of modified glass fiber comprises the following steps:
[0080] A1: 10g of glass fiber (chopped length 4mm, single fiber diameter 13um), 10mL of deionized water, 90mL of anhydrous ethanol, and 6g of vinyl trimethoxysilane were added into a reactor, the temperature was controlled at 55℃, the heat treatment was carried out for 4h, and then washed and dried to obtain vinyl glass fiber;
[0081] A2: 10 g vinyl glass fiber, 30 mL tetrahydrofuran, 2.5 g 2-mercaptoethanol, and 0.2 g azobisisobutyronitrile were added to a reaction kettle and dispersed evenly. The temperature was controlled at 55°C and the reaction was kept warm for 3 h. The mixture was filtered, washed, and dried to obtain component 1.
[0082] A3: 10 g of component 1 and 4 g of 4,4'-methylenebis(2,6-di-tert-butylphenol) were blended to obtain modified glass fiber.
[0083] Comparative Example 3 The preparation method of modified glass fiber comprises the following steps:
[0084] A1: In a nitrogen atmosphere, 10 g of glass fiber (chopped length 4 mm, single fiber diameter 13 um), 10 mL of deionized water, 90 mL of anhydrous ethanol, and 6 g of isocyanatepropyltriethoxysilane were added to a reactor, the temperature was controlled at 55 °C, the heat treatment was carried out for 4 hours, and the isocyanate glass fiber was obtained after washing and drying.
[0085] A2: 10 g of isocyanate-treated glass fiber, 6 g of 4,4'-methylenebis(2,6-di-tert-butylphenol), 0.15 g of triethylamine and 100 mL of toluene were added into a reaction kettle and dispersed evenly. The temperature was controlled at 80°C and the reaction was kept warm for 8 hours. The solvent was removed by rotary evaporation and dried to obtain modified glass fiber.
[0086] Comparative Example 4 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0087] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0088] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Comparative Example 1 was fed into the second side feed port, blended, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0089] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0090] Comparative Example 5 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0091] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0092] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Comparative Example 2 was fed into the second side feed port, mixed, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0093] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0094] Comparative Example 6 A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows comprises the following steps:
[0095] B1: 0.1 g of antioxidant 1010, 0.3 g of PP wax powder, 3.6 g of the grafting solubilizer prepared in Example 1, 19 g of the automobile water tank recycled PA66 material prepared in Example 1, and 0.5 g of the black sand prepared in Example 1 were added into a high-speed mixer and premixed to obtain a premix;
[0096] B2: 52.5 g of PA10T resin (Vicnyl 700, purchased from Kingfa Technology Co., Ltd.) was fed into the main feed port of a co-rotating twin-screw extruder using a weight loss scale, the premix was fed into the first side feed port, and 24 g of the modified glass fiber prepared in Comparative Example 3 was fed into the second side feed port, blended, extruded into granules, and dried at 120° C. for 4 h. The extrusion temperature of the twin-screw extruder was controlled at 280° C. and the extruder speed was controlled at 400 rpm to obtain an alloy material;
[0097] B3: Add the alloy material to the main feeding port of the single-screw insulation strip extruder, control the process temperature at 340℃, use an I-type mold for shaping, and control the cooling temperature at 40℃ to obtain a seamless welded thermal insulation strip for aluminum doors and windows.
[0098] Performance Testing
[0099] (1) Tensile strength: tested according to GB / T 1040.2-2006 "Test method for tensile properties of plastics", with a tensile test rate of 50 mm / min. The test results are shown in Table 1;
[0100] (2) Bending properties: Tested in accordance with GB / T 9341-2008 “Determination of flexural properties of plastics”, with a bending strength test rate of 20 mm / min. The test results are shown in Table 1.
[0101] (3) Notched impact strength: tested in accordance with ASTM D256-10 (2018) “Standard test method for determining the cantilever pendulum impact resistance of plastics”, with a pendulum range of 2.7 J. The test results are shown in Table 1.
[0102] (4) Aging treatment: The samples prepared in Examples 5-7 and Comparative Examples 4-6 were placed in a digital forced air drying oven and aged at 240° C. for 50 h. The bending properties, notched impact strength and tensile strength were tested. The test results are shown in Table 1.
[0103] Table 1: Statistical table of mechanical properties test data of Examples 5-7 and Comparative Examples 4-6
[0104]
[0105] It can be seen from Table 1 that the modified glass fiber prepared in the present application is added to the thermal insulation strip to effectively improve the mechanical properties of the material.
[0106] (5) Heat deformation temperature: tested according to GB / T 1634.2-2004 "Determination of deformation temperature of plastics under load Part 2: Plastics, hard rubber and long fiber reinforced composite materials", load 1.8MPa, heating rate 2℃ / min, test results are shown in Table 2;
[0107] (6) Melt mass flow rate: tested according to ISO 1133. Test conditions: load 1.8 MPa, heating rate 120 °C / h. Test results are shown in Table 2.
[0108] Table 2: Statistical table of physical and chemical performance test data of Examples 5-7 and Comparative Examples 4-6
[0109]
[0110] It can be seen from Table 2 that the modified glass fiber prepared in the present application is added to the thermal insulation strip, which effectively improves the temperature resistance and processing performance of the thermal insulation strip.
[0111] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a seamless welded thermal insulation strip for aluminum doors and windows, characterized in that: The steps include: S1: According to the proportion of raw material components, antioxidant, lubricant, grafting extender, automobile water tank recycled PA66 material, and black sand are premixed, and PA10T resin and modified glass fiber are added for blending, extruded into granules, and dried to obtain alloy material; S2: molding the alloy material to obtain seamless welded thermal insulation strips for aluminum doors and windows; The preparation method of the modified glass fiber comprises the following steps: A1: Add vinyl glass fiber, tetrahydrofuran, 2-mercaptoethanol and azobisisobutyronitrile into a reaction kettle and disperse them evenly. Control the temperature to 50-60°C, keep the temperature to react for 2-4 hours, filter, wash and dry to obtain component 1. A2: In a nitrogen atmosphere, the component 1, toluene, isophorone diisocyanate and dibutyltin dilaurate are added into a reaction kettle and dispersed evenly. The temperature is controlled at 30-45° C., and the reaction is kept warm for 4-8 hours. The mixture is filtered and dried to obtain the component 2. A3: Add the component 2, 4,4'-methylenebis(2,6-di-tert-butylphenol), triethylamine and toluene into a reaction kettle and disperse them evenly. Control the temperature to 70-80° C. and keep the temperature for 4-8 hours. Rotary evaporate to remove the solvent and dry to obtain modified glass fiber. The preparation method of the grafting compatibilizer comprises the following steps: adding ethylene-1-octene copolymer, maleic anhydride and initiator into a twin-screw extruder, melting and extruding and granulating to obtain the grafting compatibilizer.
2. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The preparation method of the vinyl glass fiber comprises the following steps: adding glass fiber, deionized water, anhydrous ethanol and vinyl trimethoxysilane into a reaction kettle, controlling the temperature at 50-60° C., heat preservation for 3-6 hours, washing and drying to obtain the vinyl glass fiber.
3. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The modified glass fiber accounts for 24.0-24.5% of the total mass of the thermal insulation strip.
4. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1 is characterized in that: The PA10T resin accounts for 51.2-55.6% of the total mass of the thermal insulation strip.
5. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The grafted compatibilizer is an elastomer formed by grafting maleic anhydride onto ethylene octene copolymer; the grafted compatibilizer accounts for 3.5-6.0% of the total mass of the thermal insulation strip.
6. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The preparation method of the automobile radiator recycled PA66 material comprises the following steps: the automobile radiator recycled particles are mixed with a diepoxy group chain extender EP and an antioxidant, and then added into a twin-screw extruder for extrusion and granulation to obtain the automobile radiator recycled PA66 material; the automobile radiator recycled PA66 material accounts for 18.3-19.8% of the total mass of the thermal insulation strip.
7. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The lubricant is any one of stearic acid, metal stearate, olefin wax lubricant, oleamide, and ethylene bis stearamide; the lubricant accounts for 0.2-0.4% of the total mass of the thermal insulation strip.
8. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant; the antioxidant accounts for 0.1-0.2% of the total mass of the thermal insulation strip.
9. The method for preparing a seamless welded thermal insulation strip for aluminum doors and windows according to claim 1, characterized in that: The black sand is organic carbon black obtained by treating carbon black with a silane coupling agent; the black sand accounts for 0.3-0.8% of the total mass of the thermal insulation strip.
10. A seamless welded thermal insulation strip for aluminum doors and windows, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Special material for high-fluidity high-temperature polyamide heat-insulation strip and preparation method of material
CN104497569A
High-heat-resistance high-flow nylon composite material and preparation method thereof
CN106366657A